2013
DOI: 10.1093/pcp/pct138
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell Expansion in a KRP2 Overexpressor is Mediated by Increased V-ATPase Activity

Abstract: Decreased cell numbers during leaf development often trigger increased cell size, a phenomenon called compensation. In compensation-exhibiting mutants, the unusually high cell expansion activity occurs through two different mechanisms during the post-mitotic stage of leaf development, except in the KIP-RELATED PROTEIN 2-overexpressing line (KRP2 o/e), whose cell sizes are 2-fold greater during proliferative growth. However, the molecular basis of compensated cell expansion (CCE) has not been characterized. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…11 Although the molecular nature of the first 2 classes of CCEs remains unclear, the third class, represented by KIP-RELATED PROTEIN 2 (KRP2) overexpressors (o/e), was described in our recent study. 12 We demonstrated that the unusually large cell size in KRP2-overexpressing plants relies on increased vacuolar type H + -ATPase (V-ATPase) activity. This finding increased our understanding of the molecular nature of one major pathway mediating CCE in plant leaves.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 Although the molecular nature of the first 2 classes of CCEs remains unclear, the third class, represented by KIP-RELATED PROTEIN 2 (KRP2) overexpressors (o/e), was described in our recent study. 12 We demonstrated that the unusually large cell size in KRP2-overexpressing plants relies on increased vacuolar type H + -ATPase (V-ATPase) activity. This finding increased our understanding of the molecular nature of one major pathway mediating CCE in plant leaves.…”
mentioning
confidence: 99%
“…This finding increased our understanding of the molecular nature of one major pathway mediating CCE in plant leaves. 12 The Arabidopsis genome is known to possess 7 KRP genes with low sequence similarities and distinct expression patterns. 13 11,13,14,15 We analyzed the cellular dynamism (i.e., cell number and size) in leaf primordia from 4 d after sowing (DAS) to leaf maturity (30 DAS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such compensatory coordination between cell cycling and expansion is known to occur in the leaves of many mutants and transgenic lines, and has been the topic of several investigations. For example, by considering the manner through which a cell reaches its ultimate size and performing kinematic analyses of cell size dynamism, three classes of compensation have been identified: Class I, an enhanced postmitotic cell expansion rate (seen in angustifolia [an]3-4, fugu2-1/fasciata [fas]1-5, and erecta [er]-102); Class II, an extended post-mitotic cell expansion period (seen in fugu5-1); and Class III, increase in the size of dividing cells (seen in KIP-RELATED PROTEIN 2 [KRP2] over-expressing cells) (Ferjani et al 2007(Ferjani et al , 2008(Ferjani et al , 2010(Ferjani et al , 2013a(Ferjani et al , 2013b(Ferjani et al , 2014. Furthermore, during compensation, cell-autonomous and non-cell-autonomous pathways have been identified (Kawade et al 2010, 2013, Ferjani et al 2013a.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by considering the manner through which a cell reaches its ultimate size and performing kinematic analyses of cell size dynamism, three classes of compensation have been identified: Class I, an enhanced postmitotic cell expansion rate (seen in angustifolia [an]3-4, fugu2-1/fasciata [fas]1-5, and erecta [er]-102); Class II, an extended post-mitotic cell expansion period (seen in fugu5-1); and Class III, increase in the size of dividing cells (seen in KIP-RELATED PROTEIN 2 [KRP2] over-expressing cells) (Ferjani et al 2007(Ferjani et al , 2008(Ferjani et al , 2010(Ferjani et al , 2013a(Ferjani et al , 2013b(Ferjani et al , 2014. Furthermore, during compensation, cell-autonomous and non-cell-autonomous pathways have been identified (Kawade et al 2010, 2013, Ferjani et al 2013a. Finally, the fact that compensation occurs in a wide range of plant species other than Arabidopsis, including tobacco, rice, and snapdragon, suggests that common developmental mechanisms that trigger compensation are widely conserved in angiosperms (Hemerly et al 1995, Barrôco et al 2006, Delgado-Benarroch et al 2009.…”
Section: Introductionmentioning
confidence: 99%